Monaural or binaural sound deprivation in postlingual hearing loss: Cochlear implant in the worse ear. (6th November 2015) - Canale, Andrea; Dalmasso, Giulia; Dagna, Federico; Lacilla, Michelangelo; Montuschi, Carla; Rosa, Rosalba Di; Albera, Roberto
Abstract : Objectives/Hypothesis: To determine whether speech recognition scores (SRS) differ between adults with long‐term auditory deprivation in the implanted ear and adults who received cochlear implant (CI) in the nonsound‐deprived ear, either for hearing aid–assisted or due to rapidly deteriorating hearing loss. Study Design: Retrospective study. Methods: Speech recognition scores at evaluations (3 and 14 months postimplantation) conducted with CI alone at 60‐dB sound pressure level intensity were compared in 15 patients (4 with bilateral severe hearing loss; 11 with asymmetric hearing loss, 7 of which had contralateral hearing aid), all with long‐term auditory deprivation (mean duration 16.9 years) (group A), and in 15 other patients with postlingual hearing loss (10 symmetric, 5 asymmetric with bimodal stimulation) (controls, group B). Results: Comparison of mean percentage of correctly recognized words on speech audiometry at 3 and 14 months showed improvement within each group ( P < 0.05). Between‐group comparison showed no significant difference at 3 ( P = 0.17) or 14 months ( P = 0.46). Comparison of SRSs in group A (bimodal stimulation [n = 7] and binaural sound deprivation [n = 4]) versus group B showed no significant differences at 3 (bimodal stimulation P = 0.16; binaural sound deprivation P = 0.19) or 14 months (bimodal stimulation P = 0.14; binaural sound deprivation P = 0.82). Conclusions: Speech recognition scores in monaural and binaural sound‐deprived ears did not significantly differ from ears with unilateral cochlear implantation in nonsound‐deprived ears when tested with CI alone. Improvement in the implanted worse ear indicates that it could be a potential candidate ear for cochlear implantation even when sound deprived. Level of Evidence: 4. Laryngoscope, 126:1905–1910, 2016